Preliminary assessment of marine debris pollution and coastal water quality on some beaches in Thanh Hoa province, Vietnam - Lim, Duong Thi; Nguyen, Thi Lan Huong; Nguyen, Thi Hue; Dang, Tran Quan; Nguyen, Thi Huong Thuy; Tran, Thu Thuy; Trinh, Thi Minh Trang; Dao, Ngoc Nhiem; Nguyen, Quang Bac; Mai, Van Tien (Vietnam Journal of Marine Science and Technology, 2021)
Marine debris assessment gives information about their quantity, type, and composition, which provides data to help with their management and control. The authors conducted two surveys at three beaches at Sam Son, Hai Tien, Hai Hoa) in Thanh Hoa province in March 2020 and July 2020, respectively, during an inactive and active tourism period. A total of 3,803 waste units were collected for assessment, of which plastic waste accounts for more than 98%. The density of marine debris at the idle time of tourism ranged from 0.25–1.21 items/m2. But the active tourist season recorded from 0.52–1.4 items/m2. According to the Clean Coast Index (CCI), the cleanliness of beaches was grade from average clean (i.e., Hai Tien) to filthy (i.e., Hai Hoa). The plastic debris present at these beaches was mainly porous waste derived from fishing boats and food preservation foam boxes. The results also showed that the marine debris was composed of 77% polystyrene (PS), 17% polypropylene (PP) and 6% high-density polyethylene (HDPE). The water parameters were lower than the critical values during the study period according to the QCVN 10-MT:2015/BTNMT for both periods, which indicated the coastal water quality was still suitable for recreational activities.